Analisis Pengaruh DPK, CAR, NPL, ROA dan Suku Bunga SBI Terhadap Penyaluran Kredit Perbankan (Studi Kasus pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode2009 – 2013) - Bella Anindita Apsari (Jurnal Ilmiah Mahasiswa FEB, 2014)
Bank is one of the financial institution having a major role in the world economy in the middle of a financial institution as financial intermediary between surplus unit and the deficit unit. One of the efforts of bank is credit. And this amount of credit in the character of an institution such as bank intermediation the surplus unit and the deficit unit. The source of fund from public and this should be distributed to people in form of credits. The background of this research cause credit  bank is not optimal. It can be seen from the average of loan to deposit ratio (LDR ) commercial banks in period 2009-2011 which was about at approximately 72,88 % to 76,87 % , where under prediction of Indonesian Bank. The aim of this research is  to analyze the factors that affect credit bank disbursement , by looking at the internal factor firm covering of third party funds (dpk ), capital adequacy ratio (car), non performing loan(NPL), return on assets (ROA) and on SBI interest rate external company as a factor .This research uses 10 bank are  largest asset , with a period of 2009-2011 (on annual basis). The technique analysis use e-views6 software with panel regression. The results of this research is the third party funds (DPK) have a positive effects and significant on bank credit disbursement, capital adequacy ratio (CAR) have a negative effects and insignificant on bank credit disbursement, non performing loans ( NPL ) have a negative influence and significant on bank credit disbursement, return on assets (ROA ) have a positive effects and not significant on bank credit disbursement and SBI interest rates have a positive effects and not significant to credit of bank disbursement. The Implications of the research is expected the banks must to increase their credits and sources of capital possessed in an optimum manner .And have good credit management to avoid the some credit risks. Keywoards: Bank Credit Disbursement , Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return on Assets (ROA), SBI Interest Rates